Políticas públicas para o ensino médio do estado do Rio Grande do Sul no ínicio XXI: o ensino de matemática - Barbieri, Dioneia Zanon (2016)
This study aims at investigating the curricular reforms Lessons of Rio Grande (Lições do Rio Grande) and Polytechnic High School (Ensino Médio Politécnico), elaborated and implemented, respectively, in the governments Yeda Crusius and Tarso Genro, in the state of Rio Grande do Sul, as to its commonalities and to its distances in relation to the teaching of Mathematics in high school. In order to carry out this study, at first, the researchers sought to briefly recover the history of Education in Brazil. After that, they presented a brief description of some of the official documents that base (or based) the Brazilian Educational System: the National Education Law (Lei de Diretrizes e Bases da Educação Nacional), the National Curriculum Guidelines (Diretrizes Curriculares Nacionais), the National Curricular Parameters (Parâmetros Curriculares Nacionais), the National Educational Plans (Planos Nacionais de Educação), and the Innovative High School Program (Programa Ensino Médio Inovador). Following that, we described the two curricular reforms aforementioned and conducted, based on Oliveira (2007) and Moreira (2005), the documental analysis of each official document. To do so, we developed four categories: a) educational orientations, b) contextualization and interdisciplinarity, c) teacher s continuous education, and d) evaluation. From the study of these categories, it was possible to observe the distances and commonalities in the pedagogical reforms in question, and its influences in the teaching of Mathematics in high school in the state of Rio Grande do Sul.